Exploring the Long‐Lasting Effect of Mindfulness‐Based Intervention in Very Preterm Adolescents on Executive and Socio‐Emotional Competencies. - Siffredi, Vanessa; Liverani, Maria Chiara; Fernandez, Natalia B.; Hüppi, Petra Susan; Borradori Tolsa, Cristina; Ha‐Vinh Leuchter, Russia (Child: Care, Health & Development, 2025)
Background: Very preterm (VPT) adolescents show executive and socio‐emotional difficulties that persist into adulthood. Beneficial effect of mindfulness‐based intervention (MBI) has been found in VPT young adolescents immediately after the end of the intervention. This study aims to examine the long‐term effects of an 8‐week MBI (2 to 5 years after the completion of the 8‐week MBI) on executive and socio‐emotional competencies in VPT adolescents. Methods: The 'Mindful Preterm Teens – Follow‐Up' study included 21 VPT adolescents, born before 32 weeks of gestation, who had previously completed the MBI, as well as 22 VPT and 28 full‐term adolescents (aged 13 to 18) who had never participated in an MBI. Executive and socio‐emotional competencies were assessed using self‐ and parent‐reported questionnaires, as well as using neuropsychological testing. Past and current mindfulness practices were collected via self‐ and parent‐questionnaires. Pearson's correlations were used to explore associations between current mindfulness practice and outcome measures, and group differences in outcome scores were analysed using multivariate analysis of covariance (ANCOVA). Results: In VPT adolescents who had previously completed the MBI, current mindfulness practice was generally infrequent (ranging from at least once per month to no practice). This group showed a significant association between lower levels of current mindfulness practice with reduced parent‐rated anxiety. When comparing the group of VPT adolescents who had completed the MBI with both VPT and FT participants who had not, no significant differences were observed in executive and socio‐emotional competencies. Conclusions: We observed no significant effect of MBI on the long‐term (i.e., 2 to 5 years after the end of the MBI) in VPT adolescents. Regular mindfulness pratice might be needed to maintain the immediate beneficial effect of MBI.